Soliditas Nilai Karakter Pendidikan melalui Instrumen Gambus Melayu Riau di Universitas Islam Riau - Fitriah, Laila; Ritawati, Tengku; Vivian, Yofi Irvan (Jurnal Mebang: Kajian Budaya Musik dan Pendidikan Musik, 2024)
Riau Malay Gambus. This research utilizes a descriptive qualitative approach to observe the solidity of educational character values through the Riau Malay Gambus instrument at the Islamic University of Riau. The data collection techniques employed in this research include literature review, informant selection, interviews, and documentation. Three educational character values are embedded in the Riau Malay Gambus: religiosity, discipline, and environmental concern. The religious value inherent in the Riau Malay Gambus lies in the utilization of its lyrics, which are related to the Islamic religion, stories or messages conveyed relating to Allah, prophets, and other Islamic histories. The value of discipline is evident in the students' dedication to practice and presentational efforts to achieve maximum grades.